2015
DOI: 10.1105/tpc.15.00171
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Avirulence Loci and Allele-Specific Effector Recognition Control thePm3Race-Specific Resistance of Wheat to Powdery Mildew

Abstract: In cereals, several mildew resistance genes occur as large allelic series; for example, in wheat (Triticum aestivum and Triticum turgidum), 17 functional Pm3 alleles confer agronomically important race-specific resistance to powdery mildew (Blumeria graminis). The molecular basis of race specificity has been characterized in wheat, but little is known about the corresponding avirulence genes in powdery mildew. Here, we dissected the genetics of avirulence for six Pm3 alleles and found that three major Avr loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
276
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(284 citation statements)
references
References 94 publications
7
276
0
1
Order By: Relevance
“…tritici, which has a length of approximately 1,800 cM (ref. 28). Thus, one expects one recombination event every 10 Mb in a sexual cycle.…”
Section: Competing Financial Interestsmentioning
confidence: 99%
“…tritici, which has a length of approximately 1,800 cM (ref. 28). Thus, one expects one recombination event every 10 Mb in a sexual cycle.…”
Section: Competing Financial Interestsmentioning
confidence: 99%
“…tritici . The AvrPm3 a2/f2 gene belongs to a family of 24 sequence‐divergent, but structurally related, secreted effectors (Bourras et al ., ). In transient expression assays in Nicotiana benthamiana , it was demonstrated that AVRPM3 A2/F2 is recognized specifically by the Pm3a and Pm3f alleles.…”
Section: Introductionmentioning
confidence: 97%
“…spp. ), specifically the Pm3 gene in wheat ( Triticum aestivum ) and the Mla gene in barley ( Hordeum vulgare ), suggest that distinct resistance alleles recognize highly sequence diverse effectors (Bourras et al ., ; Lu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco infiltration with Agrobacteria (strain GV3103) containing the pBART-560 p35S::LRR11-Citrine construct was performed as described (Bourras et al, 2015).…”
mentioning
confidence: 99%